انعكاس السلوك المهني لمراقبي الحسابات على المحاسبة الابداعية دراسة تحليلية - لعينة من مكاتب مراقبي الحسابات والاكادميين في اقليم كوردستان- العراق - احمد, أ.م.د. رزگار علي; عبدالله, إعداد قبل الطالب: هه‌‌وراز عمر (Sulaimani Journal for Humanities, 2023)
The study aimed to analyze and determine the extent of the auditors' commitment to the ethics of the rules of professional conduct and its reflection in creative accounting. The general framework of the study represents the problem of the study, which identified several questions about the nature of the correlation and influence between the variables of the study, the ethics of the profession and the rules of professional conduct and the limitation of creative accounting by relying on the questionnaire. For this purpose, a hypothesis designed to study five main hypotheses, and in order to verify the validity of the hypotheses, all of them subjected to multiple tests. The study used a questionnaire as a means to obtain data. The study adopted the descriptive analytical method. The main variables described, as well as the analysis of the relationships and influence between the variables, and the study sample represented by a sample of auditors and teaching staff holding postgraduate degrees in accounting and finance. As for the respondents, their number was (121) from the auditors and the teaching staff in the Kurdistan Region, which represents the study sample. The hypotheses tested through a set of statistical methods using computer programs (Amos V. 24) and (SPSS V. 24). The study reached a set of conclusions, including the results of the analysis revealed the existence of a significant and direct correlation between the variables of the study the ethics of the profession and the rules of professional conduct and the limitation of creative accounting and the presence of a moral effect on the ethics of the profession and the rules of professional conduct in limiting creative accounting. The study recommended a set of proposals, the most important of which is to strengthen the factors affecting the compliance of auditors with the rules of professional conduct and to try to push the auditors and urge them to adhere to the accounting profession and activate the supervisory role by the concerned authorities to maintain this.
Keywords: Keywords professional ethics; professional code of conduct; and creative accounting